An exploration of parents' knowledge, attitudes and practices towards the use of antibiotics in childhood upper respiratory tract infections in a tertiary Jordanian Hospital - Khawla Abu Hammour; Mariam Abdel Jalil; Walid Abu Hammour (Elsevier, 2018)
Objectives: The present study aimed to evaluate the parents' knowledge, attitudes and practices (KAP) towards the use of antibiotics for childhood upper respiratory tract infections (URTIs), at the Jordanian University Hospital. Methods: This was a cross-sectional study. During the study period, 1301 parents of young children completed a validated - structured questionnaire. Results: Gaps in common knowledge related to antibiotics and their use were noted among participants. Nearly half of respondents believed that antibiotics are void from adverse effects, while 72.4% of them believed that a child should be given an antibiotic if it develops fever, even though 60% they were aware that most URTIs were viral in nature. Parents reported that they administered antibiotics to children without medical advice most of the time for various causes, including using a previously prescribed antibiotic for a similar illness (27.1%), or based on pharmacist's recommendation (23.8%). Conclusion: The results demonstrated the need for educational interventions to increase the awareness of parents about antibiotics to reduce inappropriate use and its consequences. Keywords: Antibiotics, Attitude, Knowledge, Parents, Upper Respiratory Tract infections, Hospital